53-year-old Woman with Sjögren's Syndrome and Anti-synthetase Syndrome Manifesting as Interstitial Lung Disease - Krisdiyanto, Peter; Noor Chozin, Iin; Rakhma, Sastia; Rachma Erawati, Dini; Aditya Rahman, Perdana (Universitaas Brawijaya, 2026)
Background: Sjogren's Syndrome (SS) one of rare disease (approximately 1,0% population) that common manifest as Interstitial Lung Disease (ILD). This pathological condition has a poor prognosis, causes mortality, and is the most common complication. One of the systemic autoimmune diseases characterized by impaired function of the exocrine glands. Anti-synthetase syndrome (ASS) is an autoimmune condition, characterized by aminoacyl-transfer-RNA-synthetase antibodies accompanied by ILD, myositis, or arthritis. Case Report: A 53-year-old housewife was diagnosed with SS 3 years ago with osteoporosis and spinal compression. Complaints of dry skin, muscle weakness, back pain, joint pain, and shortness of breath after doing strenuous activities. History of treatment with Azathioprine 2 x 50 mg for 1 month and replaced with Mycophenolate mofetil (MMF) 2 x 360 mg after ILD was found on High-Resolution Computed Tomography (HRCT). Laboratory results showed anemia Hb 10.3, elevated CK-NAC levels (563 U/L), and positive anti-PL-7-Ab results. HRCT shows Usual Interstitial Pneumonia (UIP). Body-plethysmography results shows respiratory restriction (40%). Discussion: SS is identified by the presence of myositis-specific antibodies, accompanied by at least 2 conditions, ILD, inflammatory myopathy, or inflammatory polyarthritis. Anti-threonyl-tRNA-synthetase specific antibody (anti-PL-7) is one of the rarest. ILD presentation on HRCT helps identify SS or combination of ASS. The type of ILD that appears inpatients is a picture of UIP. Treatment of SS with Azathioprine is replaced with MMF after ILD is known and if progress is found, there is a place for giving anti-fibrotics. Conclusion: A 53-year-old woman with SS who found specific anti-PL-7 antibodies manifested ILD and inflammatory myopathy supports a combined diagnosis of ASS.